Sudan : First Review of Performance Under the 2007-08 Staff-Monitored Program. (IMF Staff Country Reports; Country Report, 2008)
Sudan's economic prospects are good, but risks remain. The report states that strong actions were taken for Government Finance Statistics Manuals and Guides (GFSM) implementation for monitoring domestic arrears under the Staff-Monitored Program (SMP). The need to maintain macroeconomic stability and implement strong monetary and fiscal policies are found to be essential. Higher oil prices and production have raised revenues. The need to correct past slippages and to reestablish fiscal credibility are found to be essential. Implementing delayed measures on public financial management and financial sector reform is crucial for restoring fiscal credibility and financial soundness.